Prevalence and risk factors of fractures in transfusion dependent thalassemia – A Hong Kong Chinese population cohort. Issue 4 (30th April 2022) - Lee, Samantha Lai Ka; Wong, Raymond Siu Ming; Li, Chi Kong; Leung, Wing Kwan
Abstract: Objective: To delineate the prevalence and associated risk factors of low BMD, osteoporosis/bone fragility and fracture in transfusion‐dependent thalassemia (TDT) in the Chinese population in Hong Kong. Design, Patients and Measurements: A retrospective cohort study design was employed. Patients of TDT who had serial Hologic dual‐energy X‐ray absorptiometry (DXA) from 2010 to 2016 and received regular transfusion for at least 5 years were recruited. Clinical and biochemical data, from 5 years before the first DXA scan, were retrieved from the electronic record system of the Hospital Authority, till 30 June 2020. Low bone mineral density and osteoporosis/bone fragility are defined by the ISCD 2019 position guidelines. Results: Seventy‐seven patients were included in the analysis. The fracture prevalence of TDT among the Chinese population in Hong Kong was 15.58%. Up to 55.84% of patients had low bone mineral density, and 5.19% patients had osteoporosis/bone fragility state. The median age at first fracture was 31.73 years (range 24.06–44.18 years). In the regression analysis, a higher log(10) transformation of average ferritin levels over 5 years before the first DXA scan was significantly associated with fracture occurrence regardless of bisphosphonate treatment (OR 310.73, 95% CI 3.99–24183.89, p = .010). Mean average ferritin level over 5 years was 6695.5 ± 2365.7 pmol/L (fracture group) versus 4350.7 ± 3103.2 pmol/L (non‐fracture group), p = .016. Hip and spine BMD Z ‐score did not have statistically significant association with fracture occurrence. Conclusion: Iron overloading plays an important role in adverse bone health in TDT. Dual X‐ray densitometry is insufficient in predicting fracture risk. Abstract : The cohort of this study included participants with long follow‐up period and a large sample size to assess the fracture outcomes in a succinct way. The study has demonstrated average ferritin levels over a period of 5 years was significantly associated with fracture occurrence, suggesting for an insidious process of adverse impact of iron overloading in bone health. Our data has updated the prevalence of low mineral density, osteoporosis/ bone fragility state according to ISCD 2019 position guidelines, which allowed for avoidance of over‐labelling of osteoporosis with T‐score alone. Our data has suggested that dual X‐ray densitometry is insufficient in predicting fracture risk, though data was limited by the heterogeneous timing of the bone densitometry.